Design solutions for urban densification - Kramer, Sibylle, author
The world's metropolises are home to steadily growing populations. Densification measures are one solution to the problems of urbanization, creating inner-city living space where there was none before. The smallest of gaps between buildings is utilized, perimeter block developments are completed, courtyards filled in, houses heightened and smaller structures replaced with larger ones. This process of densification preserves existing and naturally developed quarters and infrastructure, while protecting against urban sprawl and the development of soulless quarters full of new builds. In some cases, a self-contained element that clearly sets itself apart from the existing built environment is most suitable; in others, the best solution is the re-interpretation and development of the existing context. The architectural approach to each project is as unique as its context.